2010
DOI: 10.1186/1710-1492-6-s2-p23
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Semaphorin4C by Th2-stimulated B cells

Abstract: Figure 1 Relative expression of SEMA4C mRNA over GAPDH in stimulated tonsillar B cells (N=5).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Moreover, inhibition of SEMA4A - Plexin-D1 reduced lung fibrosis mediated by AKT (protein kinase B) signaling [ 38 ]. Interestingly, Another survey declared that SEMA4C could be a key player in local allergic inflammation [ 39 ]. It has also been shown that SEMA4A - Plexin-D1 contributed to the elevated IL-4 and IL-17 in patients with systemic sclerosis (SSc), and the same manner can be seen for other T CD4 + mediate diseases, including asthma, rheumatoid arthritis (RA), and multiple sclerosis (MS) [ [40] , [41] , [42] ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, inhibition of SEMA4A - Plexin-D1 reduced lung fibrosis mediated by AKT (protein kinase B) signaling [ 38 ]. Interestingly, Another survey declared that SEMA4C could be a key player in local allergic inflammation [ 39 ]. It has also been shown that SEMA4A - Plexin-D1 contributed to the elevated IL-4 and IL-17 in patients with systemic sclerosis (SSc), and the same manner can be seen for other T CD4 + mediate diseases, including asthma, rheumatoid arthritis (RA), and multiple sclerosis (MS) [ [40] , [41] , [42] ].…”
Section: Discussionmentioning
confidence: 99%